The Effect of the Guided Inquiry Learning Model on the Learning Outcomes of Grade VII Students in Biology at SMP Negeri 6 Tondano - Redemta Persila Wagetdo; Aser Yalindua; Masje Wurarah (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
This study seeks to evaluate the impact of the guided inquiry learning paradigm on the academic performance of seventh-grade students in biology at SMP Negeri 6 Tondano. This research used a quasi-experimental approach utilising a non-equivalent control group design. The study sample comprised class VII A with 25 students and class VII B with 25 students. This study's variables include the independent variable (X), which consists of users of the guided inquiry learning model, and the dependent variable (Y), which pertains to the learning outcomes of seventh-grade students at SMP Negeri 6 Tondano. Data gathering methods encompass interviews, documentation such as activity reports and pertinent data, and written assessments, including multiple-choice examinations. The hypothesis test employed to assess the difference in student learning outcomes between the experimental and control groups utilises the t-test. The mean post-test learning results for Class VII B students (experimental group) utilising guided inquiry is 82.6. In contrast, the mean outcomes for Class VII A students (control group) employing direct instruction is 77. The hypothesis test findings indicate a t-test value of 2.826, which exceeds the t-table value of 2.010 at a significance level of 0.05. According to the criteria for hypothesis testing, H0 is rejected, and H1 is approved. Consequently, it can be inferred that the guided inquiry learning model positively impacts the learning results of Class VII students in biology at SMP Negeri 6 Tondano.